NATIONAL IDEA AS A SYNTHESIS OF HISTORY AND SPIRITUALITY - Yuldoshali Rahimov (Galaxy International Interdisciplinary Research Journal, 2022)
One of the most important paradigms of modern state policy and the ideology of an established state is the need to form a national idea focused on the mobilization of the entire society. In this regard, this article systematizes the theoretical approaches to national identity that exist in foreign and domestic political science, and proposes the author’s interpretation of the category "national identity" as an organic formation or synthesis of history and spirituality.